Exploring adaptability in organizations: Where adaptive advantage comes from and what it is based upon. Issue 6 (3rd October 2016) - Tejeiro Koller, Manuel Ramón
Abstract : Purpose: The purpose of this paper is to contribute to the development of a new perspective on adaptive strategy design. It examines the concept of adaptive advantage, as such a new perspective, and seeks to improve its understanding and application. The study of its origins leads to a solid comprehension of the concept and the proposal of a certain company profile. This could serve as a foundation for further research and as benchmark for companies trying to be more responsive to change and ultimately more resilient. Design/methodology/approach: Three theories of the area of adaptability, namely, organization ecology, corporate demography and complexity-based thinking, have been studied conducting a review of the relevant literature of each one. After drawing out the individual contributions, a definition of adaptive advantage is offered and the question about its implementation in an organization is posed. Consequently, indicators of the three elements impacting adaptability, innovation culture, decision-making style and accumulated experience are measured in a sample of "old" and innovative firms. In order to do so, three questionnaires have been used, resulting in a case description of an archetype of adaptive companies. Findings: It is shown that the expected elements are present, but in a lesser degree than expected. In conclusion, the trial study shows a pattern of "old, " innovative firms, whose cultures promote innovation, are analytic and adaptive in their decision making and have relatively high levels of accumulated experience. Originality/value: This general review improves the comprehension of a complex concept currently under debate in the field of strategic planning. It explains the areas of the firm implicated in the achievement of adaptive advantage and tries to clarify a practical application of the concept.